Alleviating Soil Acidity: Optimization of Lime and Zinc Use in Maize (Zea mays L.) Grown on Alfisols. Issue 2 (19th January 2020) - Behera, S. K.; Shukla, A. K.; Dwivedi, B. S.; Cerda, A.; Lakaria, B. L.
ABSTRACT: Soil acidity, one of the causes of soil degradation, adversely affects phytoavailability of soil nutrients and crop growth in 50% of arable land of the world. There is a persistent need for alleviating the effect of soil acidity for adequate nutrient availability and proper crop growth. Addition of ameliorants like farmyard manure (FYM) and lime to acid soils affects the crop growth and nutrient availability, especially zinc (Zn) availability, by moderating soil acidity. However, the information regarding optimum quantities of lime and zinc requirement for alleviating soil acidity, proper crop growth, and Zn nutrition in acid soil is limited. Therefore, the present greenhouse pot experiments were carried out at ICAR-Indian Institute of Soil Science, Bhopal, India, in kharif season of 2015 using two acid soils (representing Alfisol order) to optimize lime and Zn application and to understand the impact of FYM and lime application on soil properties, phytoavailable Zn, biomass yield of maize, and Zn uptake, for better growth and Zn nutrition of maize. Maize was raised for 60 days with two levels of FYM (0 and 4, 500 mg kg −1 ), five levels of lime requirement (LR) (0, 1/10 th, 1/3 rd, 2/3 rd, and 1.0), and three Zn levels (0, 2.5, and 5.0 mg kg −1 ). Results revealed that FYM and lime addition significantly influenced soil properties, biomass yield, and postharvest soil extractable Zn. Lime addition at 1/3 rd LR was found optimum as biomass yield enhanced up to this level of liming. FYM addition augmented biomass yield. A higher amount of lime (2/3 rd and 1.0 LR) led to a reduction in crop Zn concentration and its uptake. The phytoavailable Zn extracted by different extractants in soils declined with increasing lime rates. Zn addition enhanced biomass yield and crop Zn concentration. The lowest and the highest amount of Zn were extracted from the soil at all levels of lime addition by diethylenetriaminepentaaceticacid (DTPA) and 0.1 M HCl, respectively. The extractable Zn was correlated significantly with biomass yield, crop Zn concentration, and its uptake. Ammonium bicarbonate DTPA (ABDTPA) proved promising extractant for estimation of Zn availability in these acid soils. This knowledge will be of use for alleviation of acid soils by the addition of the required quantity of lime and effective Zn management in acid soils for proper Zn nutrition and crop growth.